Characterization of Endophytic Bacteria Isolated from Avicennia marina’s Leaf Tissue Collected from Ekowisata Mangrove Wonorejo Surabaya, Indonesia - Dian Savitri Wina; Lewi Santoso Marvel; Antonius Yulanda; Hartatie Hardjo Popy; Jan Asad (E3S Web of Conferences, 2023)
The previous experiment showed that Avicennia marina’s leaf collected from Ekowisata Mangrove Wonorejo, Surabaya, Indonesia contained endophytes. The endophytes were known as bacteria which was demonstrated by biochemical tests based on Bergey’s manual of determinative bacteriology. This experiment aimed to characterize the three isolates of bacteria by using Deoxyribonucleic acid. (DNA )sequencing. The result showed that isolate 1 and isolate 2 were known as Bacillus subtilis with a different strain, whereas isolate 3 was considered as Bacillus sp. It was in line with the result of biochemical tests. To know the sensitivity of three isolates against antibiotics, a 30 μg tetracycline disc on Nutrient Agar that was overgrown by the isolate was used. The results showed that halo was observed on three isolates, meaning that all of them were sensitive to 30 μg tetracycline.